(untitled) (diségno, 2022)
The Polytechnic Department of Engineering and Architecture and the Science and Technology Pole of the University of Udine organized from June 13 to 17, 2022, the second PhD Summer School of the Unione Italiana per il Disegno entitled Around Palladio / Attorno a Palladio. Nuove metodologie di disegno per l’architettura. The Summer School [1], dedicated to advanced PhD training in the disciplines of representa- tion, allowed PhD students to have a direct experience with respect to advanced tools and methods for the analysis, documentation, visualization and dissemination of architectural and cultural heritage. The initiative was held in continuity with the first edition, which took place from September 24 to 28, 2018, at the National Archaeological Museum of Aquileia and the University of Trieste’s Gorizia Pole on the topic of Cultural Heritage Survey and Inclusive Representation for Museum Accessibility / Rilievo dei beni culturali e rappresentazione inclusiva per l’accessibilità museale. [read more]